Propriedades na nocicepção e na inflamação de uma fração polissacarídica sulfatada da alga marinha Acanthophora muscoides - Quinderé, Ana Luíza Gomes (2013)
Herein, a sulfated polysaccharidic fraction obtained from the marine alga Acanthophora muscoides (AmII) was evaluated using models of nociception and inflammation. The systemic toxicity of the total sulfated polysaccharides was also assessed. The antinociceptive properties were assayed using the writhing test induced by acetic acid, the formalin and the hot plate test. Swiss mice were treated with AmII (1, 3 or 9 mg/kg; i.v.) 30 min prior to either receiving an injection of 0.8% acetic acid or 1% formalin or prior to a thermal stimulus. AmII reduced the number of acetic acid-induced writhes and licking time in the second phase of the formalin test, but it did not alter the response latency in the hot plate test. The anti-inflammatory properties were assayed using the carrageenan-induced neutrophil migration into the peritoneal cavity and carrageenan- or dextran-induced paw edema models. Wistar rats were treated with AmII (1, 3 or 9 mg/kg; s.c.) 60 min prior to inflammatory stimuli. AmII reduced significantly the neutrophil migration into the peritoneal cavity. In the carrageenan-induced paw edema, AmII did not reduce the edema formation or the neutrophil migration, as assessed by the determination of myeloperoxidase levels in the paw tissue. However, AmII reduced dextran-induced paw edema during the first interval analysed. Furthermore, when AmII (500 μg) was injected (s.c.) into the paw, to verify a possible edematogenic effect, no edema was observed. Additionally, when mice were treated with the total sulfated polysaccharides from A. muscoides (20 mg/kg; i.p.) for 14 days, no consistent signs of systemic damage were observed, as revealed by body weight, liver, kidney, heart, spleen, thymus and lymph node wet weight and by biochemical, hematological and histopathological analyses. In conclusion, AmII has antinociceptive and anti-inflammatory properties and represents a potencial therapeutic agent warranting future studies.